Developing Technical Writing Skills to Engineering Students. (2015) - Rus, Dana
Abstract: The most important aspect to consider when writing a technical document is that it is essentially different from a "general" document in terms of its objectives and audience. In terms of methodology, the acquisition of writing skills within the frame of technical English inevitably follows the patterns of general English language acquisition, to which one should add some specific features dictated by the specialized uses of the technical discourse. In this respect, ESP teachers encounter the insufficiently exploited challenge of adapting the methodological tools to the specific needs of the Engineering students. The study presents the specific features of the most popular forms of written technical communication models and suggests some methodological resources which the ESP language instructor may adopt in order to build and reinforce engineering students' writing skills. The objectives of the present study are to introduce, define and explain the task of writing technical documents and highlight the importance of these types of texts in the activities related to an engineer's specific responsibilities both in a professional environment and during training; to outline the specific character of technical documents and to present and explain methodologies which can be used in teaching technical English writing skills.